Lisa's airplane trip - Gutman, Anne.; Hallensleben, Georg (New York : Knopf : Distributed by Random House, 2001)
Lisa takes an exciting airplane ride all by herself from Paris to New York.
"Originally published in France as Lisa prend l'avon by Hachette Jeunesse in 1999"--P. facing t.p.
2.5
K-3
K-3
School Library Journal
Booklist starred
Keywords: Airplanes -- Fiction; Travel -- Fiction; Dogs -- Fiction; Airplanes -- Fiction; Travel -- Fiction; Dogs -- Fiction